Mentoring Practices of Novice English Teachers - Bhandari, Bhim Lal (Journal of NELTA Gandaki, 2022)
Mentoring is a professional rapport in which an experienced professional supports novice teachers in the premature phases of their profession to develop and progress their teaching career by sharing their teaching skills, experiences and knowledge. This article examines the English language teachers’ understanding and practices of mentoring along with my experiences. I employed a descriptive phenomenological research design to explore the lived experiences of teachers about mentoring. Four English teachers teaching at the secondary level were purposively selected as the participants for the study from two community schools of Rupandehi, Nepal. I used interviews as a technique for collecting information from the participants. The finding of the study shows teachers’ positive mentoring experiences as they are satisfied with mentoring practices. The study also shows that the common mentoring practices the English teachers employed were peer support, profession-related workshops, training, conferences and seminars. The study may contribute to boost professional competency in their teaching career having effective mentoring experiences and practices with some insightful ideas.